Relative frequency, Possible Risk Factors, Viral Codetection Rates, and Seasonality of Respiratory Syncytial Virus Among Children With Lower Respiratory Tract Infection in Northeastern Brazil. Issue 15 (April 2016) - Gurgel, Ricardo Queiroz; Bezerra, Patrícia Gomes de Matos; Duarte, Maria do Carmo Menezes Bezerra; Moura, Adriana Ávila; Souza, Edna Lucia; Silva, Luciana Sobral da Silveira; Suzuki, Claudia Eiko; Peixoto, Rodrigo Buzzatti
Abstract : Abstract: Few studies, each limited to a single major city, have investigated the prevalence and seasonal patterns of different viruses among children with low respiratory tract infections (LRTI) in Northeastern Brazil. The aim of this study was to determine the frequency of respiratory syncytial virus (RSV) and of 7 other viruses in children for LRTI in 4 capitals from this region, and investigate their association with several risk factors, including meteorological data. From April 2012 to March 2013, 507 children, aged up to 24 months and hospitalized with LRTI in one of the participating centers at Aracajú, Salvador, Recife, and Maceió, had a sample of nasopharyngeal aspirate collected and analyzed for the following viruses by reverse-transcription polymerase chain reaction followed by hybridization on low-density microarrays: RSV, influenza, parainfluenza, adenovirus, rhinovirus, metapneumovirus, bocavirus, and coronavirus. The result was positive in 66.5% of cases, RSV was the most common virus (40.2%). Except for rhinovirus (17%), all other virus had frequency rates lower than 6%. Viral coinfections were detected in 13.8% of samples. Possible related risk factors for RSV infection were low age upon entry, attendance of daycare, low gestational age, and low educational level of the father. The relative frequency of viral infections was associated with increasing temperature and decreasing humidity separately, but the results also suggested both associated with increased frequency of RSV. Some of these findings differ from those reported for other regions in Brazil and may be used to guide policies that address LRTI.